2022
DOI: 10.3390/diagnostics12030570
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network-Based Automatic Analysis of Chest Radiographs for the Detection of COVID-19 Pneumonia: A Prioritizing Tool in the Emergency Department, Phase I Study and Preliminary “Real Life” Results

Abstract: The aim of our study is the development of an automatic tool for the prioritization of COVID-19 diagnostic workflow in the emergency department by analyzing chest X-rays (CXRs). The Convolutional Neural Network (CNN)-based method we propose has been tested retrospectively on a single-center set of 542 CXRs evaluated by experienced radiologists. The SARS-CoV-2 positive dataset (n = 234) consists of CXRs collected between March and April 2020, with the COVID-19 infection being confirmed by an RT-PCR test within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…There have also been attempts to apply AI to the diagnosis of COVID-19 using chest computed tomography (CT) in addition to CXR [ 25 ]. Some efforts were made to predict the outcome of COVID-19 patients using radiomics features on CXR or AI-based prediction models using CXR [ 11 , 26 , 27 , 28 ]. Similar to our study, Mushtaq et al used Conformité Européenne (CE)-certified AI software on initial CXRs to predict the mortality of COVID-19 patients and the authors demonstrated that initial CXRs could be used as a predictor of adverse outcome in COVID-19 patients [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have also been attempts to apply AI to the diagnosis of COVID-19 using chest computed tomography (CT) in addition to CXR [ 25 ]. Some efforts were made to predict the outcome of COVID-19 patients using radiomics features on CXR or AI-based prediction models using CXR [ 11 , 26 , 27 , 28 ]. Similar to our study, Mushtaq et al used Conformité Européenne (CE)-certified AI software on initial CXRs to predict the mortality of COVID-19 patients and the authors demonstrated that initial CXRs could be used as a predictor of adverse outcome in COVID-19 patients [ 3 ].…”
Section: Discussionmentioning
confidence: 99%